The taxonomic status of Farlowella colombiensis Retzer & Page 1997 with comments on species of the F. acus species group (Loricariidae: Loricariinae) - Melo‐Ortiz, Omar Eduardo; Retzer, Michael E.; Prada‐Pedreros, Saúl; Chaparro, Gustavo Adolfo Ballen (Wiley, 2025)
The genus Farlowella has been historically challenging, in part due to the difficulty in defining diagnostic characters for defining and identifying the species. Farlowella colombiensis is one such example, whose diagnostic characters are based on caudal-fin colour pattern, ventral pattern of body cover and anatomical details of the head, such as the arrangement of odontodes and the presence/absence of dorsomedian ridge. We herein reassess the taxonomic status of this species against congeners of the F. acus species group (F. acus, F. martini, F. mitoupibo, F. venezuelensis and F. vittata). We found no significant differences between F. colombiensis and F. acus in morphometric, meristic and colouration pattern, therefore rendering Farlowella colombiensis a junior synonym of Farlowella acus. We provide remarks on different species of the F. acus group in Colombia, as well as a description of sexual dimorphism in the genital papilla for the first time in the subfamily. We also provide a key to the species of the F. acus species group in Colombia.